Physical activity and sport-specific training patterns in Swedish sporting and working trial dogs—A questionnaire survey - Essner, Ann; Hesbach, Amie L.; Igelström, Helena; Kjellerstedt, Catarina; Svensson, Kristina; Westerlind, Helga (Frontiers in Veterinary Science, 2022)
Objective: To explore physical activity patterns, including exercise and sport-specific training, and management routines utilized by handlers of Swedish sporting and working dogs participating in agility, obedience, rally obedience and working trial disciplines. Procedures: Dog handlers provided information on competition-level dogs through an internet-based observational and cross-sectional survey on physical activity, sport-specific training and management. Results are reported overall and stratified by participation in specific disciplines. Results: We received 1615 replies to the questionnaire. After data cleaning, 1582 dogs (98%) remained for the analysis. Of these, 430 participated in agility, 790 in obedience, 596 in rally obedience, and 847 dogs had competed in a working trial, i.e., messenger, protection, search or tracking. Number of disciplines performed by each dog varied between one and five. Most common was participation in one (n=767, 48%) or two (n=541, 34%) discipline. Out of the dogs competing in one discipline, 38% (n=294) were considered to be specialized. The vast majority of the dogs (n=1129, 71%) received more than one hour of physical activity, e.g., walks, per day and only n=51 (3%) were never exercised off leash. Preferred self-selected gait was trot (n=907, 57%) and gallop (n=499, 32%). A fifth (n=319, 20%) never played with other dogs. The majority (n=1328, 84%) received more than one hour of vigorous physical exercise per week. Almost three quarters (n=1119, 71%) added physical conditioning. Two thirds (n=953, 60%) participated in at least three hours of sport-specific training per week and only a very small portion (n=35, 2%) trained their specific discipline less than once per week. Median total work load, i.e., all daily exercise, vigorous exercise and sport-specific training, was 16.5 hours per week. Conclusion and clinical relevance: We observe a moderate to high level of activity among the dogs, with a somewhat higher activity level among working trial dogs. Most dogs received complementary physical conditioning activities, but not all dogs were warmed up before training and competition. Our study provides valuable insights on management of sporting and working dogs in general and differences in activity patterns across disciplines.